On The Question of Contradictions in Socialist Society - Minkevičius, Jokūbas (Problemos, 1968)
In the article the essence of the law of contradictions is revealed. There the author shows how the overcoming of certain contradictions results in appearance of new ones. Although the socialist society is free of antagonistic contradictions it is, however, not at all devoid of contradictions. The overcoming of contradictions means the struggle for Communism.